Improving the Efficiency of Hospital Nursing Unit Design: an analytical study. Issue 1 (1st August 2022) - Ibrahim, E; Sherif, A; Serag Eldin, H
Abstract: The inpatient nursing unit is one of the most important departments in a hospital building. It is where patient treatment and healing occur. Improving the efficiency of the nursing unit design may improve the length of patient stay, reduce medical errors and increase patient satisfaction, thus improving the performance of the medical services provided in the hospital. This paper addresses the architectural design factors which affect performance in a typical inpatient nursing unit. A two-step approach was used in this paper. First, the factors which influence the nursing unit performance were identified from literature. Then, typical nursing unit floor plan shapes were identified. Four floor plan shapes were selected from these for analysis. Analysis focused on the factors of flexibility of operation, ease of patient monitoring, provision of patient privacy, reduction of nurse travel time, and provision of a supportive healing environment. The racetrack floor plan has shown a higher level of performance in comparison with the other floor plan shapes. It has shown superior qualities in regard to flexibility, patient monitoring, and nurse travel distances. However, for this shape to be successfully used, sound and noise control measures should be adopted to improve performance regarding patient privacy and noise disturbance. The courtyard and radial floor plan shapes provide a medium level of performance. The radial floor plan is superior in regard to patient monitoring capabilities. Although the single corridor plan has shown higher levels of sound privacy and lower levels of noise disturbance, it did not provide good flexibility, patient monitoring, and travel distances.